Efektivitas Program Kartu Prakerja dalam Membangun Sumber Daya Manusia Pasca Pandemi Covid-19 - Diyah Anggraeni; Ruslan Abdul Ghofur; Syamsul Hilal (Jurnal Informatika Ekonomi Bisnis, 2023)
This paper discusses the effectiveness of the Pre-Employment program in building human resources and the role of the Pre-Employment program in developing the quality of human resources. The purpose of this research is to determine the effectiveness of the Pre-Employment program in building resources in the midst of a human pandemic. Determine the role of the Pre-Employment program in building quality human resources in the midst of a pandemic. Using a descriptive quantitative research approach, the type of data used in this study is primary data obtained from in-depth interviews with beneficiaries of the Pre-Employment Card program. The research results obtained are pre-employment programs are less effective in building human resources. The Pre-Employment Program has a very important role in building the quality of human resources.